THE RELATIONSHIP BETWEEN ANXIETY LEVELS AND DYSPEPSIA SYNDROME IN STUDENTS - Yuliawati, Ratna; Oktavia, Istiqomah Nur; Kurniasari, Lia (Universitas Muhammadiyah Ponorogo, 2025)
Dyspepsia syndrome, a form of digestive system disorder related to psychological conditions, especially anxiety, which can directly affect an individual's perception of the physical symptoms they experience. The purpose of this study was to identify anxiety levels in students of the Public Health Undergraduate Program at the Muhammadiyah University of East Kalimantan, identify the incidence of dyspepsia syndrome, and analyze the relationship between anxiety levels and the incidence of dyspepsia syndrome. This study used a quantitative approach with a cross-sectional design, involving 208 students selected through stratified random sampling techniques, and analyzed using the Fisher's Exact Test. The results showed that most respondents were 20 years old and mostly female. Most respondents experienced mild anxiety, and as many as 88.9% of respondents experienced dyspepsia syndrome. Bivariate analysis showed a significant relationship between anxiety levels and the incidence of dyspepsia syndrome (p = 0.001). Based on these findings, it is recommended to increase awareness of the importance of mental health, as well as the provision of psychological counseling services on campus to prevent psychological impacts that can affect students' physical health and digestive system.